Preliminary Assessment of the Technical Condition of Water Supply Infrastructures - Tuhovcak, Ladislav; Kucera, Tomas; Suchacek, Tomas (Procedia engineering, 2016)
To ensure sustainability and reliability of water supply infrastructure, we must apply a basic pre-condition, which is, its continual renewal. For renewal planning, there are many methods, techniques and software tools for decision support, but most of them, in many cases, focus only on water mains. Water supply systems, however, consist of different parts and structures than just water pipes. It is therefore not appropriate to invest in the renewal planning only in relation to one part of the water supply infrastructure. The knowledge of the current technical condition of the water supply infrastructure is crucial to maintain its planned performance and optimise its maintenance and renewal. Effective detailed evaluation of the technical condition requires deployment of specialists, reliable database, considerable amount of time and instrumentation and software. Therefore, it is preferable to perform the first rapid and efficient preliminary identification of problematic areas and elements of water supply systems. This paper presents the methodology and the Technical Energy Audit (TEA Water), the effective preliminary assessment of the technical state of water supply systems (WSS). The paper presents the structure of the proposed technical indicators, the method of their determination and evaluation, including the presentation of case studies of implementing the methodology and software tool in the Czech Republic.